2016
DOI: 10.1002/j.0022-0337.2016.80.11.tb06216.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Faculty Knowledge and Perceptions of Copyright at U.S. Dental Schools: A Pilot Study

Abstract: The aims of this pilot study were to investigate current copyright training and support provided to faculty at North American dental schools and to examine faculty members' knowledge and attitudes related to specific copyright issues. In 2015, a survey with questions about faculty members' comfort about their own and their colleagues' knowledge and application of various copyright issues was designed and distributed. True/false questions were asked to determine the extent of knowledge about copyright. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…In the survey of AL staff, 51 per cent deemed comprehension as being adequate when asked about their perception of academics' understanding of copyright at their institution. This figure corresponds to that reported by Doubleday and Goben (2016) for academics reporting themselves as being "somewhat comfortable" with their knowledge of copyright.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the survey of AL staff, 51 per cent deemed comprehension as being adequate when asked about their perception of academics' understanding of copyright at their institution. This figure corresponds to that reported by Doubleday and Goben (2016) for academics reporting themselves as being "somewhat comfortable" with their knowledge of copyright.…”
Section: Discussionsupporting
confidence: 85%
“…In like vein, Sims's (2011) detailed report into copyright knowledge of, among others, library staff, researchers and, of relevance here, instructors, at one American university revealed that the majority of respondents considered themselves as having as much knowledge as most of their colleagues. However, as with Doubleday and Goben (2016), when focussing on selfassessment, Sims's study found substantial gaps in copyright knowledge, with little understanding of the basic principles of copyright law as well as confusion over classroom practice.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Algumas normas devem ser seguidas para que um caso clínico possa ser publicado. De início, é necessária a permissão para reprodução do material fotográfico do paciente ou retirado de outro autor, aprovando a utilização das imagens em periódicos científicos 22 . Em seguida, a provação do Comitê de Ética em Pesquisa (CEP), quando referente a pesquisas com seres humanos 23 .…”
Section: Normas Para a Publicação De Caso Clínicounclassified